Otherness and victimhood in the tabloid press - Vezovnik, Andreja (Dve domovini, 2017)
By using critical discourse analysis, the article focuses mainly on ways in which migrants are constructed through language in the most widely-read Slovenian tabloid newspaper, Slovenske novice (Slovenian News). The article begins with a definition of tabloid discourse and continues with an empirical exploration of how migrants are constructed as "the other" and Slovenians as victims. The empirical material covers the period from 20 August 2015 to 31 December 2015. The author establishes that tabloid discourse mainly employs binary dichotomies between "us", who are represented as victims, heroes, and heroic victims, and "them", who embody a threat to the culture and security of the majority population.
Keywords: Analiza diskurza; Begunci; Discourse analysis; human migration; migracije; Refugees; Slovenske novice; Tabloid newspapers; Tabloidi